2019
DOI: 10.1186/s12881-019-0794-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeted next generation sequencing in 112 Chinese patients with intellectual disability/developmental delay: novel mutations and candidate gene

Abstract: Background Intellectual disability/developmental delay is a complex condition with extraordinary heterogeneity. A large proportion of patients lacks a specific diagnosis. Next generation sequencing, enabling identification of genetic variations in multiple genes, has become an efficient strategy for genetic analysis in intellectual disability/developmental delay. Methods Clinical data of 112 Chinese families with unexplained intellectual disability/developmental delay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Overall, our detection rate for the pathogenic and likely pathogenic variants were limited to 27% because we scanned for variants only in the coding regions. Previous studies on ID using high‐throughput DNA sequencing revealed a conclusive diagnostic rate as 8.0–34.0% (Chérot et al, 2018; Fitzgerald et al, 2015; Gieldon et al, 2018; Han et al, 2018; Lindstrand et al, 2019; Nambot et al, 2018; Wright et al, 2015; Yamamoto et al, 2019; Yan et al, 2019). Of these, one study using WGS revealed a total diagnostic rate of 27%, which was the same as that reported in this study (Lindstrand et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our detection rate for the pathogenic and likely pathogenic variants were limited to 27% because we scanned for variants only in the coding regions. Previous studies on ID using high‐throughput DNA sequencing revealed a conclusive diagnostic rate as 8.0–34.0% (Chérot et al, 2018; Fitzgerald et al, 2015; Gieldon et al, 2018; Han et al, 2018; Lindstrand et al, 2019; Nambot et al, 2018; Wright et al, 2015; Yamamoto et al, 2019; Yan et al, 2019). Of these, one study using WGS revealed a total diagnostic rate of 27%, which was the same as that reported in this study (Lindstrand et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Of these variants, eight occurred de novo (66.7%), two showed maternally inherited X‐linked patterns (16.7%), one was autosomal dominant (8.3%), and one was transmitted in an autosomal recessive (AR) manner (8.3%). The proportion of inheritance patterns of pathogenic or likely pathogenic variants in previous studies using high‐throughput DNA sequencing analysis differs in frequency study by study from other East Asian and Western European countries, but de novo dominant variants were the most common (55–90%), while maternally inherited X‐linked variants (5–22%) and variants inherited in AR manner (0–22%) have variable frequencies, second only to de novo variants (Chérot et al, 2018; Fitzgerald et al, 2015; Gieldon et al, 2018; Han, Jang, Park, & Lee, 2018; Nambot et al, 2018; Wright et al, 2015; Yamamoto et al, 2019; Yan et al, 2019). Our study in a Japanese ID cohort also showed a high frequency of de novo variants and a similar frequency in X‐linked and AR variants.…”
Section: Discussionmentioning
confidence: 99%
“…For etiological diagnosis, according to the guideline proposed by American Psychiatric Association (APA) in 2014 [1] and Chinese Medical Association(CMA) in 2018 [16], all patients underwent systematically examinations, comprising medical history, physical examination, metabolic tests and neuroimaging study (brain MRI/CT) to exclude non genetic causes and underwent necessary genetic tests, such as G-band karyotyping, FMR1 CGG repeat testing [17], and CMA testing [18], to exclude other genetic reasons. Sanger sequencing or Trio-NGS [19,20], including targeted exome sequencing (panel) or whole exome sequencing (WES) was performed depending on clinical judgment. The details of the detection methods are reported elsewhere.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…To investigate the possibility that mutant ATRX alleles were preferentially transmitted to offspring, a meta-analysis of published pedigrees with complete reporting of family structures was conducted. data on transmission of ATRX alleles for 42 mothers were extracted from papers published between 1991 and 2019 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Probands and index cases were excluded from the calculations, as well as offspring from one mosaic mother.…”
Section: Meta-analysis Of Maternal Transmission Of Atrx Mutationsmentioning
confidence: 99%